2018
DOI: 10.1021/acs.chemmater.8b00962
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectricity and Ferroelasticity in Organic Inorganic Hybrid (Pyrrolidinium)3[Sb2Cl9]

Abstract: Perovskite-like materials exhibit desirable photophysical and electric properties that make them suitable for a remarkable breadth of applications in electronics and physics. In this contribution, we report on the multiphase ferroelectric and ferroelastic phenomena in a pyrrolidinium-based hybrid metal–organic material: (C4H8NH2)3[Sb2Cl9]. The title compound is the first pyrrolidinium derivative within the halobismuthates­(III) and haloantimonates­(III) families that is featured by the ferroelectric property. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 49 publications
3
59
0
Order By: Relevance
“…[16][17][18][19] This phenomenon is common in a variety of materials, such as zirconia 20 or oxide and fluoride perovskites, 21,22 and has been increasingly investigated in halide perovskites. [23][24][25][26][27][28][29][30][31][32] At elevated temperatures many APbX3 materials have higher symmetry, but as the material cools the R4 + phonon mode condenses, inducing permanent out-of-phase tilting of the BX6 octahedra and a spontaneous strain in the material. [33][34][35][36][37] The strain magnitude is lowered by transition to a lower symmetry phase, which in MAPbI3 is the cubic Pm-3m to tetragonal I4/mcm transition.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19] This phenomenon is common in a variety of materials, such as zirconia 20 or oxide and fluoride perovskites, 21,22 and has been increasingly investigated in halide perovskites. [23][24][25][26][27][28][29][30][31][32] At elevated temperatures many APbX3 materials have higher symmetry, but as the material cools the R4 + phonon mode condenses, inducing permanent out-of-phase tilting of the BX6 octahedra and a spontaneous strain in the material. [33][34][35][36][37] The strain magnitude is lowered by transition to a lower symmetry phase, which in MAPbI3 is the cubic Pm-3m to tetragonal I4/mcm transition.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that (C 4 H 8 NH 2 ) 3 [Sb 2 Cl 9 ] has a trigonal R 3 m crystal structure and it is built up of [Sb 2 Cl 9 ] 3– infinite layers, composed of corner-sharing SbCl 6 octahedra, and pyrrolidinium counterions balance the negative charge of the layers. 43 2D and 3D materials are more desirable for photovoltaic applications than 0D materials given their lower band gap and smaller exciton banding energy. The optoelectronic properties of perovskites can be changed with tuning by halide and A- and B-site substitution.…”
Section: Lead-free Trivalent Halide Perovskites With a 3 B 2 X 9 Stoichiometrymentioning
confidence: 99%
“…two-dimensional (2D) layers (honey-comb like corrugated sheets) (Fig. 3(b)); 72,[77][78][79][80][81][82][83][84][85][86][87][88][89] •. discrete bioctahedra (0D) (Fig.…”
Section: Rmx 4 (R : M = 1 : 1)mentioning
confidence: 99%